Effects of extrusion parameters on rheological properties, chromatism, protein solubility and microstructure of flaxseed-corn mixture - Min, Wu; Yi, Liu; Lijun, Wang; Dong, Li (International Journal of Agricultural and Biological Engineering, 2015)
As a kind of significant functional food material, flaxseed can be processed into snacks by extrusion technology. This research mainly studied the effects of different extrusion conditions: temperature, screw speed, material moisture content and proportion of added flaxseed, respectively. Moreover, the rheological properties of steady state were also investigated. Results showed that the steady state shear sweep tendency of extruded disperse system accorded to the power law model of non-Newtonian fluid. By fitting extrusion parameters and the parameters of power law model with polynomial, the maximum of consistency index and minimum of liquidity index can be gained when extruding temperature was 120C, screw speed was 100 r/min and the proportion of added flaxseed was 20%. Maillard reaction could occur in extruded melt when material moisture content was less than 18.2%, and then formed to be brown by-products; however, the Maillard reaction slowed down and color aberration decreased when the moisture content increased. Protein soluble index observably reduced after extrusion, which indicated that protein denaturation during extruding process and created hydrophobic structure. The study of scanning rheological and electron microscope explained the process of starch, protein and fat in mixture formed steady polymer during extruding process. Keywords: flaxseed, extrusion, flaxseed-corn blend, steady shear, rheological property, food processing DOI: 10.3965/j.ijabe.20150806.2067 Citation: Wu M, Liu Y, Wang L J, Li D. Effect of extrusion parameters on rheological properties, chromatism, protein solubility and microstructure of flaxseed-corn mixture. Int J Agric & Biol Eng, 2015; 8(6): 89－98.